Effectiveness of Online-Based Employee Training at the Garut District Tourism and Culture Office - Muchtar, Muchtar; Pundenswari, Pupung; Kania, Ikeu; Gusti Yandi, Ricky (ann4publisher@gmail.com, 2024)
This study examines the efficacy of providing staff at the Tourism and Culture Office in Garut Regency with online-based training. This study aims to evaluate the effectiveness of providing Garut Regency Tourism and Culture Office staff members with online training. Observations at the Garut Regency Tourism and Culture Office, resource interview techniques, and documentation studies through books, journals, scientific papers, and other sources are all used in this qualitative descriptive research project. The Garut Regency Tourism and Culture Office employees participated in online financial, archival, and structural leadership training. The Garut Regency Tourism and Culture Office staff has done an excellent job implementing online training; nevertheless, interference with the network and signal continues to persist. Employees claim that online training is beneficial because it may be completed at home or in the workplace and covers daily duties. The fact that there are still employees who need to comprehend technology and online media and who should receive further training or help if necessary creates barriers to online training in accessing and using online media.